Dissection of posterior triangle and lower deep jugular lymph node is mandatory in therapeutic neck dissection as a part of treatment for squamous cell carcinoma of oral cavity with clinically N1 neck - R., Shilpa; Moyihuddin, Azeem (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: In India oral cancer is the commonest malignant neoplasm, accounting for 20-30% of all cancers. Southern India presents the highest oral cancer incidence rates among women worldwide. Methods: This study was conducted in R. L. Jalappa Hospital and Research Centre and SDU Medical College Kolar, Karnataka. Thirty patients having oral squamous cell carcinoma with clinically N1 neck undergoing modified radical neck dissection between December 2010 and June 2012 were enrolled in the study. The objective of study was to determine whether dissection of posterior triangle and lower deep jugular lymph node is mandatory in therapeutic neck dissection as a part of treatment for squamous cell carcinoma of oral cavity with clinically N1 neck. Results: Out of 24 patients, 16 patients underwent wide excision with hemimandibulectomy. In these 16 cases, 2 patients had reconstruction with double flap while rest 14 cases with island pectoralis major myocutaneous flap. Out of remaining 8 patients, 2 patients underwent marginal mandibulectomy. In all these 8 patients, reconstruction was done using nasolabial flap in 1 patient, buccal pad of fat in 2 patients, masseter flap in 1 patient and forehead flap in 4 patients. In carcinoma anterior 2/3rd tongue, all 6 patients underwent hemiglossectomy with simultaneous modified radical neck dissection. Conclusions: It was concluded that during neck dissection, it may be oncologically safe to avoid level IV and level V clearance in buccal mucosa squamous cell carcinoma with N1 neck.